Application of the Load of Proof in Customs Value Disputes Reviewing From Customs Law and Tax Law (Analysis Of The Decision Of The Supreme Court Number 1965/B/PK/PJK/2018) - Ardiansyah Ardiansyah (Budapest International Research and Critics University, 2022)
In clarifying the burden of proof of customs value disputes, there is a Supreme Court Decision ruling that documents and evidence that were not submitted by the importer at the objection stage and cannot be validated and show no good faith and cannot be believed to be true by the Supreme Court of Justice. The research was conducted on the application of the burden of proof in the Supreme Court's decision related to customs and taxation law. The study concludes that the Supreme Court's decision is in line with the norms of proof of transaction value both in national law and in WTO/GATT provisions as well as tax law. The importer is obliged to submit data and supporting evidence of the transaction value to customs. And the consequence if the request is not fulfilled is the determination of the customs value by the customs official.